METHODOLOGICAL APPROACHES TO ANALYSIS, ESTIMATION AND PREDICTION OF THE MORAL-PSYCHOLOGICAL STATE OF PERSONNEL - Aleshchenko, V. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article discusses the methodological approaches to the analysis, evaluation and forecasting of the moral and psychological state of the personnel, objective and subjective indicators that affect its state. Analyzed are the existing methods of assessing the level of moral and psychological state of the personnel of the Armed Forces of Ukraine. It is noted that the method of expert assessment is given a special role in assessing the state of combat readiness of units (subunits). The ways of introducing relevant methods in the activities of the Ukrainian Armed Forces management system, officials, taking into account the prospects for the implementation of NATO standards and the theoretical views of domestic specialists, have been proposed.